Aplicações de coquetéis de celulases para a sacarificação enzimática do bagaço de cana-de-açúcar - Movio, Ariane Priscila [UNESP] (2014)
The first chapter of this work describes the pretreatment of sugarcane bagasse cane and evaluates its enzymatic saccharification from different enzymatic extracts of Penicillium viridicatum RFC3, Trichoderma reesei QM9414 , Thermoascus aurantiacus and Thermomyces lanuginosus CBMAI756 obtained from the solid state fermentation. Among these fermentations, the best individual result of hydrolysis efficiency was obtained with the enzymatic extract of the fungus T.aurantiacus, which was then used in the saccharification of bagasse pretreated with reactive oxygen species . The best rate of saccharification was achieved on bagasse pretreated with NaClO resultins in 19.8 % of yield, versus 12.2% in the bagasse in natura. The chapter 2 of this work describes the importance of synergism and inhibition of the enzyme in the form of β - glucosidase in the saccharification of bagasse. Synergism between the enzymatic extracts of fungi P.viridicatum and T.reesei the best combination of the two extracts was observed for the ratio 1:1, resulting in the release of 0.73 mg / mL glucose . The activities of β - glucosidase enzyme present in the extracts were analyzed for the effects of inhibition by glucose. The kinetic parameters Km and Vmax of the β-glucosidase enzyme presented, in case of T. aurantiacus Vmax of 4.60 μmol/min and Km 0.31 mM and with glucose Vmax 2.3 μmol/min and Km 0.37 mM. For the enzyme from P.viridicatum values were Vmax 166.7 μmol/min and Km 0.2 mM and with glucose Vmax 13.8 μmol/min and Km 1.2 mM. The β-glucosidase T.aurantiacus suffered from non-competitive inhibition, while P.viridicatum suffered mixed enzyme inhibition. We also evaluated the effects of fructose and glucose isomerase as suppressing the inhibitory effect of glucose. The presence of fructose resulted in a positive effect on the β - glucosidase activity of these fungi. The saccharification of sugarcane bagasse with the combination of glucose isomerase enzyme ...